2018
DOI: 10.3389/fphar.2018.01338
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Synthesis and Bioactivity Aspects of Beauvericin, a Fusarium Mycotoxin

Abstract: Beauvericin (BEA) is an emerging Fusarium mycotoxin that contaminates food and feeds globally. BEA biosynthesis is rapidly catalyzed by BEA synthetase through a nonribosomal, thiol-templated mechanism. This mycotoxin has cytotoxicity and is capable of increasing oxidative stress to induce cell apoptosis. Recently, large evidence further shows that this mycotoxin has a variety of biological activities and is being considered a potential candidate for medicinal and pesticide research. It is noteworthy that BEA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 110 publications
(165 reference statements)
2
63
0
1
Order By: Relevance
“…In order to find effective natural compounds to treat melanoma, we investigated the cytotoxic effects in A375SM cells and the underlying molecular mechanisms of BEA and BEA G 1 , which are two fungal cyclic hexadepsipeptides. Previous studies have shown that BEA can induce apoptosis in several cancer cells, such as lung cancer, colon cancer, leukemia, and hepatoma cells [10][11][12][13][14]. However, there has been no report regarding the inhibitory activities of BEA and its analogue BEA G 1 against malignant melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to find effective natural compounds to treat melanoma, we investigated the cytotoxic effects in A375SM cells and the underlying molecular mechanisms of BEA and BEA G 1 , which are two fungal cyclic hexadepsipeptides. Previous studies have shown that BEA can induce apoptosis in several cancer cells, such as lung cancer, colon cancer, leukemia, and hepatoma cells [10][11][12][13][14]. However, there has been no report regarding the inhibitory activities of BEA and its analogue BEA G 1 against malignant melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive secondary metabolite beauvericin (BEA) was originally isolated from the entomopathogenic fungus Beaveria bassiana [10]. BEA, a cyclic hexadepsipeptide mycotoxin biosynthesized from N-methyl phenylalanine and 2-hydroxyisovaleric acid, is reported to exhibit diverse biological activities, including antimicrobial, insecticidal, antiviral, antiplatelet aggregation, ionophoric, anti-inflammatory, antimelanogenesis, and antitumor effects [11,12]. Mechanistic studies on the cytotoxic effects of BEA have shown that it induced apoptosis in several human cancer cells, such as those derived from the blood, lung, colon, liver, prostate, breast, pancreas, and brain.…”
Section: Introductionmentioning
confidence: 99%
“…Beauvericin is a cyclic hexadepsipeptide that belongs to the enniatin family produced by various fungi and has many biologic activities, especially anticancer effects [ 12 ]. Beauvericin has been reported to induce the apoptosis of human non-small cell lung cancer cells and human epidermoid carcinoma cells through mitochondrial pathways, including the decrease of reactive oxygen species, loss of mitochondrial membrane potential, the release of cytochrome c and activation of caspase-9 and -3 [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Nyoike and Liburd (2013) (Nyoike & Liburd, 2013;Wyman, Oatman, & Voth, 1979 & Tirry, 2004;Nauen, Stumpf, Elbert, Zebitz, & Kraus, 2001;Uesugi, Goka, & Osakabe, 2002) demonstrated the capability of the two-spotted mite to develop up to 1,000-even 10,000-resistance fold change for some commercial acaricides like etoxazole, pyridaben, chlorfenapyr, hexythiazox and many other molecules. The insecticidal/acaricidal mode of action of beauvericin is still unknown (Wu, Patocka, Nepovimova, & Kuca, 2018), but the fact that resistance has developed slowly by the two-spotted mite, which is considered the most resistant This could back up the fact that beauvericin could have a new and unique mode of action. Accordingly, Grove and Pople (1980) demonstrated a higher efficacy of beauvericin against Aedes aegypti when compared to other hexadepsipeptide molecules with the same chemical structure.…”
Section: Discussionmentioning
confidence: 99%